Explanation:
If you plug 4 in for x into the equation, the equation becomes this:
![(4+2)-3(4-4)=6](https://tex.z-dn.net/?f=%284%2B2%29-3%284-4%29%3D6)
When you simplify the equation;
![(6)-3(0)=6](https://tex.z-dn.net/?f=%286%29-3%280%29%3D6)
Simplify it further,
![6-0=6](https://tex.z-dn.net/?f=6-0%3D6)
That is correct. 6 = 6
Hope that answered the question.
Step-by-step explanation:
the solution is in the picture
Givens
y = 2
x = 1
z(the hypotenuse) = √(2^2 + 1^2) = √5
Cos(u) = x value / hypotenuse = 1/√5
Sin(u) = y value / hypotenuse = 2/√5
Solve for sin2u
Sin(2u) = 2*sin(u)*cos(u)
Sin(2u) = 2(
) = 4/5
Solve for cos(2u)
cos(2u) = - sqrt(1 - sin^2(2u))
Cos(2u) = - sqrt(1 - (4/5)^2 )
Cos(2u) = -sqrt(1 - 16/25)
cos(2u) = -sqrt(9/25)
cos(2u) = -3/5
Solve for Tan(2u)
tan(2u) = sin(2u) / cos(2u) = 4/5// - 3/5 = - 0.8/0.6 = - 1.3333 = - 4/3
Notes
One: Notice that you would normally rationalize the denominator, but you don't have to in this case. The formulas are such that they perform the rationalizations themselves.
Two: Notice the sign on the cos(2u). The sin is plus even though the angle (2u) is in the second quadrant. The cos is different. It is about 126 degrees which would make it a negative root (9/25)
Three: If you are uncomfortable with the tan, you could do fractions.
![\text{tan(2u)} = \dfrac{\dfrac{4}{5}}{\dfrac{-3}{5} } =\dfrac{4}{5} *\dfrac{5}{-3} =\dfrac{4}{-3}](https://tex.z-dn.net/?f=%5Ctext%7Btan%282u%29%7D%20%3D%20%5Cdfrac%7B%5Cdfrac%7B4%7D%7B5%7D%7D%7B%5Cdfrac%7B-3%7D%7B5%7D%20%7D%20%3D%5Cdfrac%7B4%7D%7B5%7D%20%2A%5Cdfrac%7B5%7D%7B-3%7D%20%3D%5Cdfrac%7B4%7D%7B-3%7D)
Given:
1,5,25,61.....
To find:
The following number.
Solution:
We can see a pattern in the given sequence.
![(-1)^2+(0)^2=1+0=1](https://tex.z-dn.net/?f=%28-1%29%5E2%2B%280%29%5E2%3D1%2B0%3D1)
![(1)^2+(2)^2=1+4=5](https://tex.z-dn.net/?f=%281%29%5E2%2B%282%29%5E2%3D1%2B4%3D5)
![(3)^2+(4)^2=9+16=25](https://tex.z-dn.net/?f=%283%29%5E2%2B%284%29%5E2%3D9%2B16%3D25)
![(5)^2+(6)^2=25+36=61](https://tex.z-dn.net/?f=%285%29%5E2%2B%286%29%5E2%3D25%2B36%3D61)
Using this pattern the next term is the sum of squares of 7 and 8.
![(7)^2+(8)^2=49+64=113](https://tex.z-dn.net/?f=%287%29%5E2%2B%288%29%5E2%3D49%2B64%3D113)
Therefore, the next number is 113.
1 times 10 is 10. 10 times 10 is 100. So for those 3 models, the base is 10. All grids relate to the base 10 number system, because from left to right, the shaded part is getting bigger (increasing) by multiplying by 10. Hope this helps!
:)